1997
DOI: 10.1073/pnas.94.24.12833
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and bacterial expression of a sesquiterpene synthase cDNA clone from peppermint ( Mentha x piperita , L.) that produces the aphid alarm pheromone ( E )-β-farnesene

Abstract: ABSTRACT(E)-␤-Farnesene is a sesquiterpene semiochemical that is used extensively by both plants and insects for communication. This acyclic olefin is found in the essential oil of peppermint (Mentha x piperita) and can be synthesized from farnesyl diphosphate by a cell-free extract of peppermint secretory gland cells. A cDNA from peppermint encoding (E)-␤-farnesene synthase was cloned by random sequencing of an oil gland library and was expressed in Escherichia coli. The corresponding synthase has a deduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
1
8

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(147 citation statements)
references
References 56 publications
1
137
1
8
Order By: Relevance
“…26 In peppermint, the only by-product (δ-cadinene) produced by (E)-b-farnesene synthase in the presence of Mg 2+ was entirely absent in the presence of Mn 2+ ions. 27 In addition, the formation of sesquiterpenes such as germacrenes D and B and bicyclogermacrene from farnesyl diphosphate by germacrene D synthase in ginger (Zingiber officinale Roscoe; Zingiberaceae) is favored with Mg 2+ as cofactor, but it is inactive in the presence of Cu 2+ ions. 28 Similar negative effects of foliar Mn on δ-cadinene and foliar Cu on germacrenes D and B, and bicyclogermacrene 1676 are in agreement with the negative correlation observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…26 In peppermint, the only by-product (δ-cadinene) produced by (E)-b-farnesene synthase in the presence of Mg 2+ was entirely absent in the presence of Mn 2+ ions. 27 In addition, the formation of sesquiterpenes such as germacrenes D and B and bicyclogermacrene from farnesyl diphosphate by germacrene D synthase in ginger (Zingiber officinale Roscoe; Zingiberaceae) is favored with Mg 2+ as cofactor, but it is inactive in the presence of Cu 2+ ions. 28 Similar negative effects of foliar Mn on δ-cadinene and foliar Cu on germacrenes D and B, and bicyclogermacrene 1676 are in agreement with the negative correlation observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…It has a relatively low level of endogenous terpene biosynthesis, and much is already known about its molecular genetics and terpene emission profile (20)(21)(22)(23)(24). A gene encoding an E␤f synthase has been cloned from Mentha ϫ piperita and functionally expressed in Escherichia coli (25,26). In the latter study (26), we found the in vitro product profile of the synthase to consist of essentially pure E␤f with no other detectable sesquiterpenes, and this gene was therefore considered to be ideal for engineering production of the aphid alarm pheromone into plants.…”
Section: Resultsmentioning
confidence: 99%
“…L. esculentum cv. VFNT Cherry tomato plants (obtained as seed from John Steffens, Cornell University) were propagated from cuttings and grown under conditions as reported (11). L. esculentum cv.…”
Section: Methodsmentioning
confidence: 99%